The Model of Guidance and Counseling Service Strategy and its Effect on Improving Students' Learning Memory - Harahap, Akhir Pardamean; Utami, Chadiza Auliana; Aulia, Rahmi; Fauziyah, Tryana; Safitri, Hariana (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This research aims to design and develop a model of guidance and counseling service strategies that can improve students' learning recall. This research uses a qualitative research method with a literature study approach. This research was conducted in 2024. The data collection process uses screening of various sources, namely national and international journals. Data analysis uses content analysis, which aims to identify the focus of the research. The results showed that guidance and counseling services are a series of professional activities carried out systematically and planned with the main objective of helping individuals, especially students, deal with various problems that hinder their development and learning process. This study concluded that guidance and counseling services that use various psychological and educational strategies, such as stress management techniques, mnemonic methods, and concentration exercises, proved effective in improving students' learning memory. This research also contributes to developing guidance and counseling theory, especially in improving students' memory.